EVALUASI KAMPUNG UNGGULAN DIKELURAHAN TENGGILIS MEJOYO KECAMATAN TENGGILIS MEJOYO KOTA SURABAYA - Kurniawati , Vidya Rahma (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
The evaluation program was carried out to assess the performance of Surabaya city government policies based on William N Dunn's theory which has 6 indicators. Effectiveness relates to the success of operations in the public sector which has a major impact on public services. Efficiency involves the proper use of time and resources. Adequacy shows the extent to which people's needs are met. Equity relates to the fair distribution of benefits. Responsiveness is important in meeting the needs of benefited groups. Appropriateness refers to the program's goals and underlying assumptions. The evaluation was carried out to improve the welfare of the community in the Tenggilis Mejoyo sub-district by taking into account the desires, needs, hopes and demands of the community. Maximizing the duties and functions of program organizers is important for improving service quality and communicating with the community to convey hopes and demands to local governments.